La figura del sucesor del Gran Rey en la Persia aqueménida - García Sánchez, Manel (Gerión. Revista de Historia Antigua, 2006)
Classical sources are rich in data about the Successor to the throne in the Achaemenid Empire. Thanks to other sources such as royal inscriptions, Babylonian documents or the reliefs in Persepolis, we do not only know something more about the Great King’s successor, but they also enable us to test the reliability of the classics, deciding in each case if it is possible or not to carry prudence to the extremes on a succession which was marked, too often, by fratricidal struggle and harem intrigues.